Intangible Cultural Heritage (ICH) of cocos Malays in Tawau, Sabah - Hj Mohd Ariffin, Noor Aziah; Osri, Nurul Ain; Salleh, Nurul Hamiruddin (American Scientific Publishers, 2017)
This paper is part of ongoing research to explore the unique intangible cultural heritage (ICH) and practices of the Cocos Malays in Tawau, Sabah. As an emigrated community that came from Cocos (Keeling) Island to settle down in North Borneo (Sabah), Cocos Malays originated from various ethnicities, mostly of Malay origin with Islamic practices. In 1963, they became an independent community after joining Malaysia. Their ICH and practices are a mixture of English-Scottish, Malay and Javanese. The paper attempts to discuss the Cocos Malays’ ICH and practices after the emigration until now. Their present ICH and practices were not only influenced from the Cocos (Keeling) Island but also of the assimilation with the local culture and lifestyle. This study was done through archival research and fieldwork data collection (in-depth interview and non-participatory observation) with the local residents. The paper explains that most of the Cocos Malays’ ICH and practices were still maintained from their ancestry, but certain practices have changed to suit their current lifestyle, environment and Islamic teachings.